2018
DOI: 10.1002/ame2.12032
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer and super‐enhancer: Positive regulators in gene transcription

Abstract: Enhancer is a positive regulator for spatiotemporal development in eukaryotes. As a cluster, super‐enhancer is closely related to cell identity‐ and fate‐determined processes. Both of them function tightly depending on their targeted transcription factors, cofactors, and genes through distal genomic interactions. They have been recognized as critical components and played positive roles in transcriptional regulatory network or factory. Recent advances of next‐generation sequencing have dramatically expanded ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 147 publications
(217 reference statements)
1
41
0
Order By: Relevance
“…SE was primarily isolated via the Rank Ordering of SE (ROSE) algorithm in murine embryonic stem cells (ESCs) in 2013 [3,4]. It is strongly occupied with aberrant high levels of master transcription factors (TFs) (Oct4, Sox2 and Nanog), active histone marks [histone H3 lysine 4 monomethylation (H3K4me1), histone H3 lysine 27 acetylation (H3K27ac)], and transcription regulator factors (cyclin-dependent kinases (CDK)7, Mediator (MED)1, bromodomaincontaining protein 4 (BRD4), polymerase II (Pol II) and p300) [5,6]. Currently, SE identification is mainly dependent on chromatin immunoprecipitation followed by sequence analysis (CHIP-seq) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…SE was primarily isolated via the Rank Ordering of SE (ROSE) algorithm in murine embryonic stem cells (ESCs) in 2013 [3,4]. It is strongly occupied with aberrant high levels of master transcription factors (TFs) (Oct4, Sox2 and Nanog), active histone marks [histone H3 lysine 4 monomethylation (H3K4me1), histone H3 lysine 27 acetylation (H3K27ac)], and transcription regulator factors (cyclin-dependent kinases (CDK)7, Mediator (MED)1, bromodomaincontaining protein 4 (BRD4), polymerase II (Pol II) and p300) [5,6]. Currently, SE identification is mainly dependent on chromatin immunoprecipitation followed by sequence analysis (CHIP-seq) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that PAF1, as a Pol IIassociated factor, indirectly regulates the transcription of these enhancers by binding to Pol II, thereby inhibiting the synthesis of eRNA and weakening the long-acting trans-promoting effect of eRNA on the target gene promoter. Considering that eRNA has a low abundance value, the value of the trans-promoting effect of eRNA is debated and needs further study [33]. More importantly, the study also found that the relative occupancy level of PAF1 at the enhancer was much higher than that of Pol II, suggesting that the regulation of PAF1-induced enhancer activity is likely mediated by a mechanism that does not involve Pol II.…”
Section: Discussionmentioning
confidence: 85%
“…A recent report showed that the negative transcriptional regulation of the IER5 gene at its promoter region was abolished, which resulted in increased IER5 transcription upon the IR of HepG2 cells [15]. With the development of tumor genomics, an increased number of activated enhancers have been found in many malignant tumors, promoting gene transcription exponentially in a variety of ways [33]. Coincidentally, such activated enhancers have been found near the IER5 gene locus and rapidly promote transcription of the IER5 gene under the induction of external stimuli in several solid tumors, including CC [16].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most prominent of long-range chromatin interactions in ES cells are those of clusters of enhancers that function together, known as super-enhancers (also referred to as stretch enhancers) (Parker et al, 2013;Peng & Zhang, 2018). Super-enhancers are prevalent in ES cells, and are reorganized upon exit from a pluripotent state to facilitate cellular differentiation and specification, as shown through promoter capture experiments (Novo et al, 2018).…”
Section: Long-range Chromatin Interactions Are Critical For Regulatiomentioning
confidence: 99%